Beauty Meets Technology: The Impact of Fit Confidence and Augmented Reality on User Continuance - Rany, Tarysha Aulya Putri; Angelia, Dinda Ayu Sieradianto (Universitas Airlangga, 2025)
As augmented reality (AR) technology becomes increasingly integrated into e-commerce, virtual makeup try-on applications offer users a more personalized and immersive shopping experience. This study examines the influence of fit confidence and perceived augmentation on continuance usage intention among Generation Z users in Indonesia, grounded in the Stimulus–Organism–Response (SOR) framework. Using a quantitative research design, data were collected through structured online questionnaires targeting users who have interacted with AR-based virtual makeup try-on features from beauty brands and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0 using 124 samples. The results show that fit confidence significantly enhances both utilitarian and hedonic value, while perceived augmentation only increases utilitarian value and directly influences continuance usage intention. Furthermore, hedonic value but not utilitarian value significantly drives continuance usage intention, and perceived ease of use strengthens the effects of fit confidence on both utilitarian and hedonic value. Theoretically, the findings extend the SOR framework by demonstrating that fit confidence plays a more dominant role than perceived augmentation in shaping both utilitarian and hedonic value within AR-based beauty applications. Practically, beauty brands and e-commerce platforms should focus on enhancing the accuracy and realism of AR try-on features, as well as designing more enjoyable and engaging user experiences. Improving perceived ease of use is also essential, as it intensifies the positive impacts of fit confidence on user value perceptions, ultimately encouraging sustained engagement with virtual makeup try-on technologies.